C-28/C-30 oxidized cycloartanes from the leaves and twigs of Caloncoba dusenii Gilg. (June 2021) - Nguetsa, Leonel Zeufack; Mpetga, James D. Simo; Bitchagno, Gabin Thierry M.; Tadjuidje, Jules Delain; Groß, Jonathan; Lenta, Bruno Ndjakou; Opatz, Till; Sewald, Norbert; Tene, Mathieu
Graphical abstract: Highlights: The phytochemicals of a medicinal plant, Caloncoba dusenii, were investigated. Four new cycloartane-type triterpenes were characterized by spectroscopic methods. C-28/C-30 oxidized cycloartanes. The new compounds shared the same core structure. Abstract: Four hitherto unreported cycloartane-type triterpenes (1-4 ) with C-28/C-30 oxidized methyl groups together with two known compounds (5 -6 ) have been obtained from the leaves and twigs of Caloncoba dusenii Gilg. The compounds were isolated through extraction and silica gel column chromatography. Their structures and relative stereochemistry were determined by extensive use of spectroscopic techniques including IR, 1D and 2D-NMR as well as mass spectrometry. This is the first report of C-28/C-30 oxidized positions in cycloartanes from nature.